انعكاسات تقلبات أسعار النفط على التوازنات الاقتصادية الكلية في الجزائر- دراسة تحليلية - بن ناصر, عبد الحميد; مصداع, راضية (جامعة الوادي - University of Eloued, 2023)
يعتبر قطاع المحروقات العمود الفقري للاقتصاد الجزائري حيث تشكل العائدات النفطية أهم مصدر لتمويل مختلف الخطط التنموية في الجزائر، ونظرا لعدم استقرار السوق النفطية العالمية فإن الاقتصاد الجزائري مرهونا بتقلبات أسعار النفط وأزماته، ولهذا فقد هدفت الورقة البحثية إلى الإحاطة بمدى تأثر المتغيرات الاقتصادية الكلية للاقتصاد الجزائري بالتقلبات التي تشهدها أسعار النفط في السوق العالمية، حيث اعتمدنا في دراستنا على المنهج الوصفي التحليلي في التعامل مع المعطيات والإحصائيات ذات الصلّة بالموضوع. وقد خلصت الدراسة إلى أن المتغيرات الاقتصادية الكلية ( الميزانية العامة، الميزان التجاري، الناتج المحلي الإجمالي، التضخم) للاقتصاد الجزائري تتعرض للاختلال السلبي في توازناتها نتيجة للتقلبات التي تتعرض لها أسعار النفط في السوق العالمية خاصة في حالة استمرار انخفاض الأسعار، مما يستدعي البحث عن مصادر لتنويع الاقتصاد الجزائري خارج قطاع المحروقات. The fuel sector is considered the backbone of the Algerian economy as oil revenues constitute the most important source of financing various development plans in Algeria. Due to the instability of the international oil market, the Algerian economy is related to the fluctuations in oil prices and crises. The research paper aimed at taking to consideration of the extent to which the macroeconomic changes in the Algerian economy were affected by the fluctuations in oil prices on the international market. The study concluded that the macroeconomic variables (public budget, trade balance, gross domestic product (GDP) and inflation) of the Algerian economy which are exposed to negative imbalances due to fluctuations in oil prices in the international market, especially in case of continued price decline, which necessitates seeking resources to diversify the Algerian economy outside the oil sector
Implications of oil price fluctuations on Algeria's macroeconomic balances - Analysis
مقال
Keywords: أسعار النفط ; السوق النفطية ; قطاع المحروقات في الجزائر ; الاقتصاد الجزائري: Oil prices, the oil market, the Algerian oil sector and the Algerian economy.